PENDIDIKAN NILAI KONTEKS PLURALISME NILAI TINJAUAN TEOLOGI MORAL - Paul Klein (Studia Philosophica et Theologica, 2003)
Value education is indispensable to the today world which currently promotes pluralism. The Weltanschauung is plural and randomly diffused. Consequently, shift of value (Wertwandel) occurs inevitably. The Catholic Church is concerned with what we call “indifference” that poisons people in such a way that moral value then turns to an only subjective one. Value is often meant as that which is positively useful, worth, good for quality of life. The postmodern period however sets a condition that such quality of life is always diffused. Everybody has his own standard of quality of life. This is the reason why moral theology should elaborate value education in spite of Wertwandel. The article discusses the said topics in three parts: 1) shift of value (Wertwandel) in postmodern time; 2) theories of Werwandel; and 3) some concluding theses of how the Church should cope the problem of Wertwandel.